Reinforcing gut integrity: A systematic review and meta-analysis of clinical trials assessing probiotics, synbiotics, and prebiotics on intestinal permeability markers - Zeinab Ghorbani; Nargeskhatoon Shoaibinobarian; Morvarid Noormohammadi; Kate Taylor; Asma Kazemi; Ali Bonyad; Sara Khoshdooz; Ulrike Löber; Sofia K. Forslund-Startceva (Pharmacological Research)
Background: Given the magnitude and variety of chronic metabolic disease linked to increased intestinal permeability, appropriate strategies to reinforce gut barrier function are urgently needed. Methods: This systematic review and meta-analysis explores the effects of pro- and synbiotic, or prebiotic administration, on various intestinal permeability markers. Systematic searches across the Medline and Scopus databases were performed from 1961 to January 2023. The review included data from 46 published studies on pro- and synbiotics, and 22 studies on prebiotics. 46 The meta-analysis calculated standardized mean differences (SMD) along with 95 % confidence intervals (95 %CIs) using a random-effects model to evaluate the average effect sizes (ES). To analyze heterogeneity, we employed Galbraith plots and performed the Cochrane Chi-squared test. Results: The analysis on 24 trials (28 ES, n = 1603) revealed a significant reduction in lipopolysaccharide levels following pro- and synbiotics consumption with high heterogeneity and very low certainty of evidence (SMD (95 %CI) = -0.54 (-1.01, −0.07); I2 (%) = 94.4). Synthesis of 13 trials showed zonulin levels were significantly lowered after pro- and synbiotics consumption with high heterogeneity and moderate certainty of evidence (15 ES, n=778) (SMD (95 %CI) = -0.49 (-0.79, −0.18); I2 (%) = 74.9). Following prebiotics supplementation, a significant reduction in lipopolysaccharide levels was observed, with high heterogeneity identified from data including 16 RCTs (n = 792; SMD (95 %CI) = -0.88 (-1.28, −0.47); P < 0.001; high certainty of evidence; I2 (%) = 85.7; P-heterogeneity< 0.001). Conclusion: This meta-analysis revealed promising findings regarding the efficacy of pro- and synbiotic and prebiotic supplements in alleviating “leaky gut”.